POGIL-Based Learning Tools to Improve Critical Thinking Skills and Self-Efficacy on Salt Hydrolysis Material - Evriza, Dita Lestari; Prodjosantoso, A. K. (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
To carry out a learning process that can improve students' skills, appropriate chemistry learning tools are needed. This research aims to determine the characteristics and feasibility of POGIL-based learning tools, analyzing students' critical thinking abilities and self-efficacy before and after using POGIL-based learning tools. The research method used 4-D development model (Define, Design, Develop, and Disseminate). The subjects were 11th grade science student. Design were used pretest-posttest control group design. Learning tools developed are valid with a percentage of 93.7% in the construction aspect, 90% in the content aspect, and 100% in the language aspect. There was an increase in students' critical thinking skills and self-efficacy after using POGIL-based learning tools with the percentage of students' effective contribution in critical thinking skills being 30.5% and to self-efficacy 69.2% (both showed high contribute). This indicates that POGIL-based learning tools are feasible to improve students' critical thinking skills and self-efficacy.